Effect of Oxygenate Additive on Diesel Engine Fuel Consumption and Emissions Operating with Biodiesel-Diesel Blend at Idling Conditions - Mahmudul, H. M.; Hagos, F. Y.; R., Mamat; M. M., Noor; I. M., Yusri (IOP Publishing, 2017)
Biodiesel is promising alternative fuel to run the automotive engine but idling is the main problem to run the vehicles in a big city. Vehicles running with idling condition cause higher fuel supply and higher emission level due to being having fuel residues in the exhaust. The purpose of this study is to evaluate the impact of alcohol additive on fuel consumption and emissions parameters under idling conditions when a multicylinder diesel engine operates with the diesel-biodiesel blend. The study found that using 5% butanol as an additive with B5 (5% Palm biodiesel + 95% diesel) blends fuel lowers brake specific fuel consumption and CO emissions by 38% and 20% respectively. But the addition of butanol increases NOx and CO2 emissions. Based on the result it can be said that 5% butanol can be used in a diesel engine with B5 without any engine modifications to tackle the idling problem.